MEAS APPROACH IN THE NHT TYPE COOPERATIVE LEARNING TO IMPROVE THE PROBLEM- SOLVING SKILL AND DEVELOP THE RESPONSIBLE CHARACTER FOR THE STUDENTS OF XI - Muhammad Iqna Hibatallah; Sumargiyani Sumargiyani (Universitas Ahmad Dahlan, 2018)
Problem-solving abilities of the students who are still limited to things often appear alone. They lack a sense of responsibility for what became the obligations as a student becomes a problem that became the focus of this research. This research aims to improve the ability of problem-solving and developing character of the responsibility of the student. This research is a Classroom Action Research (CAR) implemented in cycles with cycle one consists of 3 meetings. The subject is an odd semester of Class XI IPA B Islamic Senior High School (MA) Ali Masum school year 2017/2018. The data collection techniques are using observation instruments (observation), interviews, and documentation tests. Analytical techniques descriptive data is done by qualitative and quantitative. The results showed that learning mathematics with the MEAs approach to NHT type cooperative learning could improve problem-solving ability. The results of the study are presented as follows: a) the ability to understand the problem increased from 89.69% to 95.20%, b) the ability to plan the problem solving increased 71.46% to 80.21%, c) the ability to carry out procedures increased 61.46% to 71.04% d) the ability to Recheck the results increased 50.00% to 70.42%. One for the character of responsibility, there is an increase that is from 2.26 (Less Good) in cycle I to 3.37 (Very Good) in cycle II.